الإعلان الالكتروني في الصورة الذهنية المدركة للمنظمة / دراسة ميدانية على مشتري الأجهزة الالكترونية في مدينة دمشق/ - ALjasem, Hasan (Latakia University Journal - Economic and Legal Sciences Series, 2019)
أثر عناصر الإعلان الالكتروني في الصورة الذهنية المدركة للمنظمة / دراسة ميدانية على مشتري الأجهزة الالكترونية في مدينة دمشق/ حسان الجاسم يتناول البحث مفهوم الإعلان الالكتروني الذي يعد من أكثر وسائل الترويج جاذبيه وانتشار، ويشكل أداة تنافسية هامة داعمة لجهود المنظمة الترويجية، ومؤثراً فاعلاً على سلوك المستهلكين، وخاصة في ظل البيئة التنافسية المعاصرة. ويهدف البحث الى معرفة تأثير عناصر الإعلان الالكتروني على الصورة الذهنية المدركة من قبل العميل، من خلال التعرف على تأثير نوع الإعلان الالكتروني ومحتواه وطبيعة المواقع التي يظهر عليها، وربطها مع الصورة الذهنية المدركة للمنظمة. من اجل اظهار حجم التأثير والدور الذي تلعبه عناصر الإعلان الالكتروني. وتوصل البحث الى مجموعة من النتائج المهمة كما يلي: - وجود علاقة ارتباط وتأثير لكل عنصر من عناصر الإعلان الالكتروني متمثلة بــ (نوع الإعلان الالكتروني، محتوى الإعلان الالكتروني، طبيعة المواقع التي يظهر عليها الإعلان الالكتروني) في الصورة الذهنية المدركة من قبل العميل. - تفسر المتغيرات المستقلة مجتمعة (نوع الإعلان الالكتروني، محتوى الإعلان الالكتروني، طبيعة المواقع التي يظهر عليها الإعلان الالكتروني) 97.3 % من تباين المتغير التابع (الصورة الذهنية المدركة للمنظمة من قبل العميل) في حال تجاهل أثر المتغيرات المستقلة الأخرى. The research deals the concept of electronic advertising, which is one of the most popular means of promotion and spread, and constitutes an important competitive tool supportive of the organization's promotional efforts, and an effective influence on consumer behavior, especially in the contemporary competitive environment. The purpose of the research is to know the effect of the elements of electronic advertising on the mental image perceived by the customer by identifying the impact of the type of electronic advertisement and its content and the nature of the sites that appear on them, and linking them with the mental image of the organization. In order to show the magnitude of the impact and role played by the elements of the electronic advertisement. The research concluded a series of important results as follows: - The existence of a correlation and impact relationship for each element of the electronic advertisement represented by (the type of electronic advertisement, the content of the electronic advertisement, the nature of the sites on which the electronic advertisement appears) in the mental image perceived by the customer. - The independent variables combined (the type of electronic advertisement, the content of the electronic advertisement, the nature of the sites on which the electronic advertisement appears) represent 97.3% of the variance of the dependent variable) mental image perceived by the customer (if the effect of other independent variables is ignored.